ANALYSIS OF FACTORS INFLUENCING THE PERFORMANCE OF NATIONAL PRIVATE BANKING IN INDONESIA, MODERATED BY THE USE OF FINTECH - Maretta Yuraska Sinulingga; Khaira Amalia Fachrudin; Nisrul Irawati (CV. RADJA PUBLIKA, 2025)
The purpose of this study is to analyze the